THE IMPORTANCE OF CORPORATE IMAGE TOWARDS CUSTOMER SATISFACTION IN THE MALAYSIAN TAKAFUL INDUSTRY - Nur Hafifa Iswati Ishak; Nur Qurratul’ Aini Ismail (International Journal of Accounting, Finance and Business, 2022)
Customer satisfaction is one of the critical aspects that has long been discussed in any business. Although it is often studied, its study is still interesting and still not outdated. This is because it is a key strategy whether the company is able to stay in business or not. Unfortunately, studies on customer satisfaction in the Malaysian Takaful industry are still limited. As a company that is highly dependent on customers, the topic of customer satisfaction is something that cannot be avoided. Therefore, this study aims to provide a conceptual paper on a corporate image as a determinant of customer satisfaction. The corporate image variable was chosen because the Takaful carries a different image from the conventional insurance. Hence, the researcher would like to see the relationship between these two elements in the Takaful industry in Malaysia. A total of 30 questionnaires were submitted to one of selected Malaysia's government agencies. Preliminary data were examined using PLS-SEM. The variable corporate image was found to be reliable and valid for further research. This study will help future researchers determine customer satisfaction among Takaful Malaysia customers.